A Compact and High-Efficiency Design of 0.915/2.45 GHz Dual-Band Shunt-Diode Rectifier for Wireless Power Transfer - Nguyen, Dang-An; Seo, Chulhun (IEEE microwave and wireless components letters, 2022)
In this letter, a novel structure is proposed for designing dual-band (DB) concurrent operation for the single shunt-diode rectifier configuration, at two highly spaced separate frequency bands, that is, 0.915 and 2.45 GHz for wireless power transfer (WPT). The structure consists of two main parts. The first part uses three transmission lines (TLINs) to match simultaneously optimal impedances from the diode side to the source of 50 Ω. The matching TLIN parameters are investigated in the closed-form design equations. The second one acts as a tuning mechanism using a capacitor connected in shunt with the diode to adjust optimal impedances for validating the first-part TLIN parameters in practice. The HSMS2860-based prototype shows that the highest power conversion efficiency (PCE) is achieved at 82.57% and 71.85% for 0.9 and 2.4 GHz, respectively, with the input power of 14 dBm and the resistance load of 620 Ω. The 50%-over PCE remains within a wide dynamic range of around 14 dB for both frequencies. Compared to the previous state-of-the-art designs, the proposed design exhibits advantages of compactness and high efficiency.